(untitled) (Scientific journal of the Fergana State University, 2024)
The article considers climate as a landscape-forming factor and components and studies the importance of climate in the formation of paragenetic landscapes of the Fergana Valley. A lot of literature on this topic and long-term climate data were analyzed. Climatic changes in the Fergana Valley and their impact on the formation of paragenetic landscapes were studied and appropriate conclusions were drawn. Based on climate data, a wind map of the Fergana Valley was generated using GIS technologies